Multiple job holding, local labor markets, and the business cycle - Barry T. Hirsch; Muhammad M. Husain; John V. Winters (IZA Journal of Labor Economics, 2016)
About 5 % of US workers hold multiple jobs, which can exacerbate or mitigate employment changes over the business cycle. Theory is ambiguous and prior literature is not fully conclusive. We examine the relationship between multiple job holding and local unemployment rates using a large Current Population Survey data set of workers in urban labor markets during 1998-2013. Labor markets with high unemployment have moderately lower rates of multiple job holding. Yet no relationship between multiple job holding and unemployment is found within markets over time, with near-zero estimates being precisely estimated. Multiple job holding is largely acyclic.
Keywords: J21; 330; Multiple jobs; Local labor markets; Business cycle